Oviposition behavior and microstructure of the eggs of Simulium dinellii (Joan) (Diptera: Simuliidae) (2015)
Little is known about the oviposition habits and egg structure of Neotropical members of the Simuliidae family. The oviposition behavior of Simulium dinellii (Joan) was observed near at Otún Quimbaya, Colombia. Small groups of females hovered about 2 cm above the water surface to oviposit. Some of these females had been capture and the eggs were obtained. These eggs were counted, measured and processed by scanning electron microscopy. Subtriangular eggs had a latticework of polygons on the endochorionic surface. Chorionic differences between the eggs of S. dinellii and the few previously studied species suggest potential taxonomic value of egg microstructure